مدارس کے نصابِ تعليم کو در پيش جديد تحديات کا جائزہ: Urdu: Contemporary Challenges for Madārīs Curriculum - Syed, Dr. Azizur Rahman (Al Basirah, 2022)
The role of religious schools i.e. Madaris and their education system i.e. Dars e Nizami in the subcontinent is immense. They have played a great part in the promotion of knowledge, and spreading literacy, especially in the Sciences of Quran, Hadith, Islamic Jurisprudence, Arabic language, and Literature, which includes research in these areas. Its impact on society cannot be omitted from history. In this paper, we will discuss the historical background of Madaris and Dars e Nizami, its evolution, and its current situation, along with the idea for betterment in it, with a few comments regarding a few changes from the senior clerics of the system. We will also discuss the importance of this change. In the end, we have given a few suggestions to the new graduates of Madaris, that will clear the picture of their pathway to life and broader their spectrum.